Ameliorating Effect of Azilsartan on Cisplatin -Induced Ocular Toxicity in Male Rats - Mahmood, Naza; Noor Majid Raheem Kareem1, (Iraqi Journal of Pharmaceutical Sciences, 2023)
Objective: To evaluate the protective effect of Azilsartan against Cisplatin-induced ocular damage by ameliorating the oxidative stress and inflammation status, as well as to compare two different doses of Azilsartan to the Resveratrol. Fifty-six male Wister albino-rats, weighing 270±30 g. The rats were allocated at random into seven groups (n=8 per group), as follows: Group 1 (Healthy control) was given 0.5% CMC orally for the 14 days. Group 2 (Positive control) was given a single injection of 7mg/kg Cisplatin intraperitoneally and then 0.5% CMC orally for the following 14 days. Group 3 was given 3.5mg/kg Azilsartan orally for the following 14 days. Group 4 was given 7mg/kg Azilsartan orally for the following 14 days. Group 5 was given a single injection of 7mg/kg Cisplatin intraperitoneally and then 3.5mg/kg Azilsartan orally for the following 14 days. Group 6 was given a single injection of 7mg/kg Cisplatin intraperitoneally and then 7mg/kg Azilsartan orally for the following 14 days. Group 7 (standard) was given 25mg/kg/day Resveratrol orally for following 14 days.Azilsartan at low dose (3.5mg/kg) showed a significant reduction in IL-1β pro-inflammatory marker level, whereas there was no significant effect on MDA and SOD levels in cisplatin-induced ocular damage. Histologically, there were significant reduction in inflammatory exudates, edema, and inflammatory cells infiltration with both doses. Additionally, there were no significant difference among Azilsartan only received groups and Resveratrol group. Azilsartan shows a promising anti-inflammatory effect in ocular tissue in Cisplatin experimental rat models by significantly reducing IL-1β overexpression, through its potent AT1receptor blocking effect. However, Azilsartan showed a slight effect on MDA levels and marginal effect on SOD levels in Cisplatin-induced ocular toxicity. Furthermore, Azilsartan at a low dose slightly mimicked the effect of resveratrol on normal ocular tissue, suggesting an advancement in prophylactic application in ocular injury.Keywords: Azilsartan, IL-1β, Cisplatin, Ocular Toxicity